2004
DOI: 10.1080/02705060.2004.9664919
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Substrate Composition and Current Velocity on Macroinvertebrates in a Semi-Artificial System

Abstract: We investigated the influence of substrate composition and current speed on the composition of macroinvertebrate communities under controlled hydraulic conditions using a semi-artificial system. Two sizes of substrate material (20 mm and 50 mm mean diameter) in five combinations were used to present variable substrata composition. Additionally, water velocity was set at three different levels-0.4, 0.6, and 1.0 ms-1. Current speed influenced composition, diversity, and variety of macroinvertebrates; substrate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In contrast, habitats with fine substrate support few macroinvertebrate taxa: this is related to habitat instability, detritus shortage, and unavailability of refugia ( Principe et al, 2007;Chakona et al, 2008). Similarly, several other studies conducted elsewhere have reported a strong correlation between substrate type and macroinvertebrate communities (Ciutti et al, 2004;Jun et al, 2016). indicated that substratum degradation can perturb the macroinvertebrate community even when water quality remains good.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast, habitats with fine substrate support few macroinvertebrate taxa: this is related to habitat instability, detritus shortage, and unavailability of refugia ( Principe et al, 2007;Chakona et al, 2008). Similarly, several other studies conducted elsewhere have reported a strong correlation between substrate type and macroinvertebrate communities (Ciutti et al, 2004;Jun et al, 2016). indicated that substratum degradation can perturb the macroinvertebrate community even when water quality remains good.…”
Section: Discussionmentioning
confidence: 92%
“…Water velocity, for example, presents a direct physical force to the organisms and affects other in-stream factors such as food and sediment delivery, and oxygen content Belmar et al, 2013;Pan et al, 2013). In addition, variation in substrate composition, in particular, is essential for the existence of many macroinvertebrate species because substrata provide shelter, food sources, and protection from predators (Ciutti et al, 2004;Jun et al, 2016).…”
Section: Introductionmentioning
confidence: 99%